Inside the Latest Edition of the Computer Journal. (13th February 2019) - Unknown
Abstract: With Professor Stephen Furber as its Editor-In-Chief, the new Computer Journal features a broad selection of papers including an exploration of random walks and a proposed extension to harmonised state identifiers